2023
DOI: 10.1371/journal.pone.0286454
|View full text |Cite
|
Sign up to set email alerts
|

Aged black garlic extract inhibits the growth of estrogen receptor-positive breast cancer cells by downregulating MCL-1 expression through the ROS-JNK pathway

Abstract: The black garlic is produced from the raw garlic by Milliard reaction at high temperature (~60–90°C) and humidity (~70–90%). In this process, the pungent odor and gastrointestinal irritation effects of the raw garlic are reduced. At the same time, unstable compounds such as allicin are converted into stable organosulfur compounds with antioxidant activity. Previous studies have confirmed that black garlic extract has anti-tumor effects and could inhibit the proliferation of various tumor cells, including breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The described effect and antitumor potential of SAC is unique for cancer cell models. Yang et al [60] studied the effects of ABGE, the water-soluble components of mature black garlic extract that is S-allyl cysteine (SAC) and S-allyl mercaptocysteine (SMAC). In the normal mammary cell line MCF-10A, they observed that ABGE had no inhibitory effect on the growth of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The described effect and antitumor potential of SAC is unique for cancer cell models. Yang et al [60] studied the effects of ABGE, the water-soluble components of mature black garlic extract that is S-allyl cysteine (SAC) and S-allyl mercaptocysteine (SMAC). In the normal mammary cell line MCF-10A, they observed that ABGE had no inhibitory effect on the growth of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no anti-proliferative and pro-apoptotic effects were demonstrated in the MCF-10A breast cancer cell line [16]. In a study on three lung cancer cell lines (H1975, H520, A549), water and alcohol extracts also showed negligible anti-proliferative properties [46].…”
Section: Anti-cancer Properties Of Black Garlic (Bg)mentioning
confidence: 97%
“…It has been shown that mature black garlic extract inhibits the proliferation, migration, invasion, and metastasis of ER+ breast cancer cells in the MCF-7 and MDA-MB-361 cell lines [16]. Moreover, it stimulates apoptosis in ER+ breast cancer cells via the inhibition of the expression of anti-apoptotic proteins MCL-1 and BCL-2, while stimulating the expression of pro-apoptotic proteins BIM and BAK [16]. The reduction in MCL-1 expression was mediated by JNK activation caused by an increase in the amount of reactive oxygen species in cancer cells [16].…”
Section: Anti-cancer Properties Of Black Garlic (Bg)mentioning
confidence: 99%
See 2 more Smart Citations